Autoreactive T cells to citrullinated HSP90 are associated with interstitial lung disease in rheumatoid arthritis. (2nd July 2018) - Chen, Juan; Song, Shuli; Liu, Yongliang; Liu, Dehao; Lin, Yihua; Ge, Shengxiang; Ascherman, Dana P.
Abstract: Aim: Previous analysis of comparative anti‐citrullinated heat shock protein 90 (citHSP90) antibody profiles between bronchoalveolar lavage fluid and serum indicates that the lung plays a direct role in shaping the immune repertoire of rheumatoid arthritis‐associated interstitial lung disease (RA‐ILD). Methods: To address the contribution of citHSP90β‐specific T cells in this process, we evaluated in vitro cytokine responses to citHSP90β in RA patients with different stages of ILD as well as in controls with non‐RA connective tissue disease‐associated ILD (CTD‐ILD). Cultures derived from whole blood were individually stimulated with HSP90β, citHSP90β, citrullinated BSA, or no antigen. The concentrations of 13 cytokines and chemokines in the plasma supernatant were then measured using Luminex xMAP technology. Results: CitHSP90β induced significantly higher levels of interferon‐γ (IFN‐γ) levels in RA‐ILD (interstitial lung abnormalities = 2 + 3) groups compared to the RA‐no ILD group ( P = 0.01), but did not stimulate the production of other cytokines ( P > 0.05). Furthermore, citHSP90β did not stimulate the production of IFN‐γ or other cytokines in those individuals with non‐RA CTD‐ILD. Conclusion: Overall, the production of IFN‐γ by T cells stimulated with citHSP90β demonstrates a bias toward TH1 immune responses that are likely involved in the pathogenesis of RA‐ILD.